Nutritional status, maternal knowledge, and chewing habits as factors associated with primary tooth persistence in children aged 6–12 years - Elfi Zahara; Andriani Andriani; Intan Liana; Cut Ratna Keumala; Agus Hendra Al Rahmad (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Primary tooth persistence during the mixed dentition phase may influence occlusion and functional masticatory patterns. There is little community-based evidence for the combined effects of nutrition, maternal knowledge, and chewing behavior. This study aimed to determine the relationship between these factors and primary tooth persistence in children aged 6–12 years. A cross-sectional study was conducted in elementary schools in the Ingin Jaya District of Aceh Besar from September to October 2025. The sample included 120 children. They were identified during clinical examination as having persistent primary teeth. Anthropometric analysis was performed to assess nutritional status using BMI-for-age z-scores (BAZ), and a structured questionnaire was used to assess maternal knowledge and chewing habits. All data were analyzed using chi-square tests, and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. The prevalence of primary tooth persistence was 60.0%, which is relatively high compared to several school-based reports. Underweight (OR= 4.6) and overweight/obese children (OR= 4.2) were more likely to have persistent asthma than children with normal nutritional status (p= 0.002). Low maternal knowledge and poor chewing habits were also significantly linked, with chewing habits showing the strongest association (OR= 7.0; p < 0.001). In conclusion, nutritional status, maternal knowledge, and chewing behavior were significantly related to the persistence of primary teeth. Longitudinal studies are suggested to clarify these causal associations.